34-(7-x)=x+17-(5-x)

Simple and best practice solution for 34-(7-x)=x+17-(5-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 34-(7-x)=x+17-(5-x) equation:



34-(7-x)=x+17-(5-x)
We move all terms to the left:
34-(7-x)-(x+17-(5-x))=0
We add all the numbers together, and all the variables
-(-1x+7)-(x+17-(-1x+5))+34=0
We get rid of parentheses
1x-(x+17-(-1x+5))-7+34=0
We calculate terms in parentheses: -(x+17-(-1x+5)), so:
x+17-(-1x+5)
determiningTheFunctionDomain x-(-1x+5)+17
We get rid of parentheses
x+1x-5+17
We add all the numbers together, and all the variables
2x+12
Back to the equation:
-(2x+12)
We add all the numbers together, and all the variables
x-(2x+12)+27=0
We get rid of parentheses
x-2x-12+27=0
We add all the numbers together, and all the variables
-1x+15=0
We move all terms containing x to the left, all other terms to the right
-x=-15
x=-15/-1
x=+15

See similar equations:

| 3x/2-5=x | | x2+12=76 | | 5+30x+10-5x=16x+25-4 | | 5(x+1)=6x-3+x | | t/4-2=16t= | | 1+6x/4+1/2-x/4=4x+7/5-2/10 | | a/6+1=16a= | | x+1,28=5,9 | | 9m+10=100m= | | 5m-15=8m | | 6(x-3)-(x+4)=4 | | 5y-11=34y= | | 3(6x+3)-5(3x-4)=5+2(x+3) | | 8.75x+7=24.5 | | 4(x–7)=x+20 | | 9x+(x-7)=3(5x-4)-(11-3x) | | 2y-17=7-6y | | 6(x-3)-(x-4)=4 | | 3x-1/2+x+5/3=3x+9/4 | | 3(6x+2)-5(3x-4)=7+2(x+5) | | x-5(x-3)=5x-3 | | 30-2x=x+15 | | 3x–8=12–x | | 8×-12=-5x+12 | | 8y÷6=4y-1 | | 0.5^x=0.6 | | 21+x=2@ | | 6(f+5)−=(f−6) | | 13d+3=7d+51 | | 5(5g+2)/4=40 | | 24.6=4c-9 | | 11d+7=5d+19 |

Equations solver categories